DOES NON-PARTICIPATION EQUAL APATHY? RE-EXAMINING NON-INVOLVEMENT IN COLLECTIVE ACTION THROUGH A SYSTEMATIC LITERATURE REVIEW (SLR) - Akhmad Saputra Syarif (Faculty of Psychology, Diponegoro University, 2026)
Many researchers have noted a drastic decline in individual participation in collective action. Nevertheless, social psychology scholars have primarily focused on studying collective action, often overlooking that inaction is not always the opposite of collective action. Inaction carries its own nuances. Failure to understand inaction can lead to misjudgments about social and political dynamics, particularly within the context of collective action. Without sufficient comprehension of inaction, individuals may struggle to develop effective strategies for mobilizing the masses to achieve group-oriented change. Consequently, the primary goals of collective action risk being hindered or even failing entirely. This study aims to bridge the gap in the literature on inaction by utilizing two databases: Scopus and Web of Science. The findings reveal inconsistencies in the definitions of inaction and the antecedents of inaction, which were examined from 326 articles and narrowed down to 13 selected articles. Additionally, the researchers conducted a review of the limitations of prior studies and provided recommendations for future research.